Strategi Tata Kelola Kawasan Daya Tarik Wisata Khusus (KDTWK) Gilimanuk Menuju Destinasi Pariwisata Berkelanjutan - Wahyundi, Rega Aldiaz; Widana, Ida Bagus Gede Agung; Suasapha, Anom Hery (Journal of Applied Science in Tourism Destination, 2023)
Objective: This research aims to determine priority strategies for the Gilimanuk Tourism Destination Area in its efforts towards sustainable tourism destination. Methodology: This methodology employs a qualitative approach using SWOT and QSPM analysis techniques. Data were collected through structured interviews with informants, direct observation in the field, and documentation. Results: The results of the study show that there are 28 internal and external conditions obtained from data collection. SWOT analysis resulted in ten strategies from internal and external conditions, namely integrating unique products with the port, forming a sustainable tourism task force, themed nature-based events, prioritizing management of the village tourism object, planting endemic plants, branding strategy, focusing on domestic tourist length of stay, conducting risk planning, conducting market research, and participating in human resource training programs. QSPM analysis indicates that the prioritized strategy is to design and package unique tourism products that integrate with the Gilimanuk Port. Limitations: This study has not discussed each aspect of sustainable tourism in greater depth with a focus on the Gilimanuk Tourism Destination Area.